2016
DOI: 10.6118/jmm.2016.22.3.146
|View full text |Cite
|
Sign up to set email alerts
|

Serum Thyroid Stimulating Hormone Levels Are Associated with the Presence of Coronary Atherosclerosis in Healthy Postmenopausal Women

Abstract: ObjectivesMenopause is a natural aging process causing estrogen deficiency, accelerating atherogenic processes including dyslipidemia. Prevalence of thyroid dysfunction is also high in postmenopausal women, and it is known to elevate the risk of cardiovascular disease (CVD). Therefore, we are to study on the associations in between serum thyroid stimulating hormone (TSH) and prevalence of CVD in postmenopausal women who have normal thyroid function.MethodsWe performed a retrospective review of 247 Korean postm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
3
4
0
1
Order By: Relevance
“…Similarly, positive correlation was also found between TSH and lipid profiles in euthyroid Chinese [30], Spanish [31] and Korean [32]. Our results, in agreement with the findings from the study of Chon et al [33], showed that serum TSH had no relationship with FPG and BMI. Other studies also investigate the relationship between serum TSH and BP in euthyroid population.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, positive correlation was also found between TSH and lipid profiles in euthyroid Chinese [30], Spanish [31] and Korean [32]. Our results, in agreement with the findings from the study of Chon et al [33], showed that serum TSH had no relationship with FPG and BMI. Other studies also investigate the relationship between serum TSH and BP in euthyroid population.…”
Section: Discussionsupporting
confidence: 92%
“…Because estrogen is the primary hormone responsible for CVD in menopausal women [9], we further analyzed the association between estrogen levels and cardiometabolic risk factors. Estradiol Elevation of serum thyroid-stimulating hormone (TSH) is common in post-menopausal women [24], and serum levels of TSH associate positively with cardiometabolic risk factors even in post-menopausal women with normal thyroid function [25,26]. Therefore, we analyzed the association between FSH and cardiometabolic risk factors after adjustment for age, body weight, and TSH.…”
Section: Association Between Estradiol Levels and Cardiometabolic Rismentioning
confidence: 99%
“…С учетом данных об увеличении риска развития ССЗ при приеме пероральных контрацептивов в зависимости от длительности их приема [15], поколения препарата [16], а также наличие таких ФР, как курение, АГ, гиперлипидемия, СД и отягощенная наследственность [17,18], можно считать, что перечисленные факторы способствовали увеличению риска развития ИМ у женщин с сохраненной менструальной функцией в нашем исследовании. Обращает внимание более чем в 2 раза чаще встречаемая патология щитовидной железы в группе женщин в постменопаузе, что можно объяснить большими инволюционными изменения в этой группе и соответствует данным литературы об увеличении частоты тиреопатий с возрастом [19,20]. Однако считать данные изменения дополнительным триггером в развитии ИМ в этой группе пациенток, по-видимому, преждевременно, учитывая очень невысокую частоту изменений уровня гормонов щитовидной железы (гипер-или гипофункция наблюдалась всего у 5,0 % пациенток из 1-й группы и 8,2 % из 2-й группы).…”
Section: Discussionunclassified